Nilai-nilai Pendidikan Karakter dalam Al Qur’an dan Hadits - Anshory, Muhammad Isa; Miftahurohman, Miftahurohman; Luthfi, Moh (Lembaga Yasin AlSys, 2025)
Character education is a planned effort to build identity and strengthen students' character. It is an endeavor to help students understand the values of human behavior in relation to God, themselves, and others. The purpose of this study is to explore the values of character education derived from verses of the Qur'an and Hadiths, which can serve as a foundation for human development within the community. The study focuses on identifying Qur'anic verses and Hadiths that reinforce character building and interpreting their meanings as narrated by scholars of Hadith to serve as foundational data. The findings indicate that character education is essential because education not only aims to nurture intelligent students but also seeks to instill character and courtesy in daily life. If students possess strong character, the nation will benefit, as students are the future generation of the country. Therefore, they must build their character from an early age so that as future leaders, they are not only intelligent but also possess good moral character. For this reason, instilling character values in students must begin as early as possible, during a period when children absorb practical knowledge as preparation for their future.